SPR platform based on image acquisition for HER2 antigen detection. (20th December 2016) - Monteiro, Johny P; Predabon, Sheila M; Bonafé, Elton G; Martins, Alessandro F; Brolo, Alexandre G; Radovanovic, Eduardo; Girotto, Emerson M
Abstract: HER2 antigen is a marker used for breast cancer diagnosis and prevention. Its determination has great importance since breast cancer is one of the most insidious types of cancer in women. HER2 antigen assessment in human serum is traditionally achieved by enzyme-linked immunosorbent assay (ELISA method), but it has some disadvantages, such as suppressing the thermodynamic–kinetic studies regarding the antibody–antigen interaction, and the use of labeled molecules that can promote false positive responses. Biosensors based on surface plasmon resonance (SPR) are sensitive optical techniques widely applied on bioassays. The plasmonic devices do not operate with labeled molecules, overcoming conventional immunoassay limitations, and enabling a direct detection of target analytes. In this way, a new SPR biosensor to assess HER2 antigen has been proposed, using nanohole arrays on a gold thin film by signal transduction of transmitted light measurements from array image acquisitions. These metallic nanostructures may couple the light directly on surface plasmons using a simple collinear arrangement. The proposed device reached an average sensitivity for refractive index (RI) variation on a metal surface of 4146 intensity units/RIU (RIU = RI units). The device feasibility on biomolecular assessment was evaluated. For this, 3 ng ml −1 known HER2 antigen concentration was efficiently flowed (using a microfluidic system) and detected from aqueous solutions. This outcome shows that the device may be a powerful apparatus for bioassays, particularly toward breast cancer diagnosis and prognosis.